Right Bochdalek congenital diaphragmatic hernia: a tertiary center's experience over 13 years - Alshaima Alghamdi; Enaam Raboe (SpringerOpen, 2021)
Abstract Background Right Bochdalek congenital diaphragmatic hernia (RB-CDH) is far less common than left Bochdalek congenital diaphragmatic hernia, accounting for only 13% of cases. There are limited published data on the outcomes and survival rate of RB-CDH. We aimed at investigating the clinical characteristics and analyzing the risk factors of survival in neonates with RB-CDH treated in our center over a period of 13 years. Results Fifteen infants with RB-CDH were identified. Most of the patients were full term (74%). The mean birth weight was 2.90± 0.72 kg. The ratio of male to female was 2:1. The mean APGAR score at 1 min was 5.31±2.34, and 7.30±1.59 at 5 min. Ten patients (67%) were imaged by antenatal ultrasound. Eleven patients (73.33%) survived to go for surgical repair. The hernia sac was found in 5 patients (45%). Most hernial defects were closed in a primary fashion. The mean age at the operative repair was 8.11±9.90 days. The average NICU stay for all patients was 40.47±50.38 days. The mean follow-up period was 20.45±9.34 months. Three patients had postoperative complications. The total survival rate in neonates with RB-CDH was 9/15 (60%). Nine out of 11 (82%) neonates survived after surgical repair. Four patients (27%) died before surgical repair. Ventilation-related bilateral pneumothorax was a contributing cause of death in three patients. Birth weight was found lower in the non-survivor's group (P < 0.05). Moreover, the degree of pulmonary hypertension was more severe among non-survivors. No statistical significance was observed between other variables and mortality. Conclusion We found that low birth weight and the presence of severe PHTN were risk factors for mortality in neonates with RB-CDH. These results are in line with previous studies on prognostic factors in CDH. Ventilator-related pneumothorax appears to be a significant contributing cause of death. Long-term follow-up studies of infants born with RB-CDH are needed as small number of cases limits large-volume RB-CDH studies.